The China population and labor yearbook, - Cai, Fang; Wang, Meiyan, 1975- (Chinese Academy of Social Sciences yearbooks. Population and labor, 2012)
This English-language volume is an edited collection of articles from the 2010 Chinese-language volume of the Green Book of Population and Labor. It examines recent developments in the Chinese demographic transition and its implications, especially for the labor market.